Carving Positive Changes: Knowledge and Attitudes of Mothers of Toddlers through Nutrition Counseling - Br Ginting Munthe, Novita; Sembiring, Iskandar Markus (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Complementary Feeding is food and drinks given to babies who have reached the age of 6 months and above to fulfill their nutritional needs. Therefore Complementary Feeding is only introduced to babies after they reach the age of 6 months or older. Complementary Feeding represents the transitional stage from breastfeeding to family foods gradually, both in terms of types and frequency of provision, portion sizes, and the form of food that is suitable for the age and digestive capacity of the baby. The purpose of this study is to identify the impact of counseling on MP-ASI on the knowledge and attitudes of mothers of toddlers aged 0-24 months at Nurtiana Ginting Clinic from December 2023 to March 2024. This research method uses an experimental approach with a pre-experimental design known as the one-group pretest-posttest design. In this approach, before counseling, respondents were asked to fill out questionnaires before (pretest) and after (posttest) counseling. Subsequently, the researcher compared the results of the pretest with the posttest. The research sample consisted of 38 mothers who had toddlers aged 0-24 months. Bivariate data analysis used the Wilcoxon test because the data were not normally distributed. Initially, only 5 respondents (13%) had good knowledge. However, after counseling, the number of respondents with good knowledge increased to 34 people (89%). The attitudes of mothers before counseling showed that 11 respondents (29%) had good attitudes, while after counseling, the number of respondents with good attitudes increased to 32 people (84%). The results of bivariate analysis using the Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). Thus, it can be concluded that there is a significant influence on the knowledge and attitudes of mothers of toddlers after counseling. These findings indicate that nutrition counseling is effective in carving positive changes in the knowledge and attitudes of mothers of toddlers. The implication of this research is the need for broader and more focused nutrition counseling programs to support the health and nutrition of toddlers.